Home and work neighbourhood environments in relation to body mass index: the Multi-Ethnic Study of Atherosclerosis (MESA). Issue 10 (18th July 2013) - Moore, Kari; Diez Roux, Ana V; Auchincloss, Amy; Evenson, Kelly R; Kaufman, Joel; Mujahid, Mahasin; Williams, Kayleen
Abstract : Background: Little is known about the neighbourhood characteristics of workplaces, the extent to which they are independently and synergistically correlated with residential environments, and their impact on health. Methods: This study investigated cross-sectional relationships between home and workplace neighbourhood environments with body mass index (BMI) in 1503 working participants of the Multi-Ethnic Study of Atherosclerosis with mean age 59.6 (SD=7.4). Neighbourhood features were socioeconomic status (SES), social environment (aesthetic quality, safety and social cohesion) and physical environment (walking environment, recreational facilities and food stores) derived from census data, locational data on businesses and survey data. Paired t tests and correlations compared environments overall and by distance between locations. Cross-classified multilevel models estimated associations with BMI. Results: Home neighbourhoods had more favourable social environments while workplaces had more favourable SES and physical environments. Workplace and home measures were correlated (0.39–0.70), and differences between home and workplaces were larger as distance increased. Associations between BMI and neighbourhood SES and recreational facilities were stronger for home environment (p≤0.05) but did not significantly differ for healthy food, safety or social cohesion. Healthy food availability at home and work appeared to act synergistically (interaction p=0.01). Conclusions: Consideration of workplace environment may enhance our understanding of how place affects BMI.